PERBANDINGAN UJI METABOLIT SEKUNDER PADA EKSTRAK BUAH, KULIT, DAN DAUN MAJA DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Dwi Rindi Atika (Jurnal Insan Cendekia, 2021)
Introduction Some plants in Indonesia contain secondary metabolites and antioxidants, one of which is the Maja Plant. The part of the maja plant used in this research is the structure of the plant which includes the fruit, skin and leaves because it is thought to have antioxidant content. Purpose this study was to compare secondary metabolites found in the fruit, skin and leaves of maja. And to determine the antioxidant activity in these samples. Method experimental study method was used in this research. The population used is the maja plant. Samples were obtained from the Slerok Village, Tegal City, Central Java using the simple random sampling technique. Results The results yield extracts of maja fruit, skin, and leaves were 48,5%, 90,4% and 32,8%, respectively. The fruit, skin and leaf extracts of maja have the same secondary metabolite content in the form of tannins, alkaloids (Wagner), and vitamin C. While the IC50 obtained in the fruit, skin and leaf extracts of maja are 2897,3434 ppm, 7321,49 ppm, and 37,0937 ppm. Conclusion of this study is that there are secondary metabolites in the extracts of fruit, skin and leaves of maja. And the strongest antioxidant activity is found in maja leaf extract. Suggestion Further researchers are expected to be able to carry out research again with different extraction methods in order to know the results of different extraction methods.